A Novel Role of IGF1 in Apo2L/TRAIL-Mediated Apoptosis of Ewing Tumor Cells. (3rd October 2012) - van Valen, Frans; Harrer, Henning; Hotfilder, Marc; Dirksen, Uta; Pap, Thomas; Gosheger, George; Humpf, Hans-Ulrich; Jürgens, Heribert
Abstract : Insulin-like growth factor 1 (IGF1) reputedly opposes chemotoxicity in Ewing sarcoma family of tumor (ESFT) cells. However, the effect of IGF1 on apoptosis induced by apoptosis ligand 2 (Apo2L)/tumor necrosis factor (TNF-) related apoptosis-inducing ligand (TRAIL) remains to be established. We find that opposite to the partial survival effect of short-term IGF1 treatment, long-term IGF1 treatment amplified Apo2L/TRAIL-induced apoptosis in Apo2L/TRAIL-sensitive but not resistant ESFT cell lines. Remarkably, the specific IGF1 receptor (IGF1R) antibody α -IR3 was functionally equivalent to IGF1. Short-term IGF1 incubation of cells stimulated survival kinase AKT and increased X-linked inhibitor of apoptosis (XIAP) protein which was associated with Apo2L/TRAIL resistance. In contrast, long-term IGF1 incubation resulted in repression of XIAP protein through ceramide (Cer) formation derived from de novo synthesis which was associated with Apo2L/TRAIL sensitization. Addition of ceramide synthase (CerS) inhibitor fumonisin B1 during long-term IGF1 treatment reduced XIAP repression and Apo2L/TRAIL-induced apoptosis. Noteworthy, the resistance to conventional chemotherapeutic agents was maintained in cells following chronic IGF1 treatment. Overall, the results suggest that chronic IGF1 treatment renders ESFT cells susceptible to Apo2L/TRAIL-induced apoptosis and may have important implications for the biology as well as the clinical management of refractory ESFT.